Thе Cycle of St. Demetrius in the Patriarchate of Peć: Part One - Pajić, Sanja R. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The Saint Demetrius Church, a part of the complex of The Patriarchate of Peć, was built by the Serbian Archbishop St. Nikodim (1317–24) as his mausoleum. Monumental painting originates from the time of the building of the church 1322–24, and was partially repainted in1619/20. There are written sources, archaeological remains and iconography about St. Demetrius of Thessaloniki, including the scenes of martyrdom and miracles. Scholars know about 13 cycles sofar, made between the middle of 11th and the end of 14th century, on the territory of the Byzantine and Serbian medieval state. They have been preserved to a different level, some of the scenes were presented independently. The research has greatly been made difficult due to the fact that the original cycle from the Basilica in Thessaloniki, the main centre from which the cult of the saint spread, does not exist anymore, although some information about it was provided by the frescoes, before they were destroyed in fire in 1917. One more textual source, which must be taken into consideration when researching the cycle, are epigrams, which were made by the famous Byzantine writer Manuel Files in the first half of 14th century. The cycle of patrons in the church of St. Demetrius in Peć was painted on the north and south wall of naos above the zone of standing figures. From the original 8 scenes, 5 compositions were preserved from the hagiography and one miracle scene. Those frescoes were: St. Demetrius before Maximian, St. Demetrius blesses St.Nestor, St. Nestor fighting Lyaeus, Martyrdom of St. Demetrius, Death of St. Demetrius (?), and St. Demetrius defends Thessaloniki from the attack of the enemy. The two beginning scenes were made between 1322–24, whereas the others were completely or partly repainted in 1619/20. The cycle starts with the scene St. Demetrius before Maximian (the legend has been preserved). The same theme was painted on the miniature in Menologium of Despot Demetrius Palaelogоs (MS. Gr.th. f. 1, fol. 54v and fol. 55r, between 1330–35), and fresco cycles in Byzantine churches in Mistras (the St. Demetrius Church or Metropolis, around 1270–85), Thalames (the Prophet Elijah Church, the end of 13th century or around 1300) and in Serbian Marco`s monastery (the St. Demetrius Church, 1376/77), as well as on the icon of St.Demetrius from Sophia (Alexander Nevsky Crypt Museum, 14th century or later). In churches in Kitti (the Sergios and Bacchos Church, around 1262–85) and in Krokees (the St. Demetrius Church,1286), both in Greece, the identification of the scene is not certain, due to the great damage of the frescoes. All the compositions follow the same iconographic scheme: the emperor is sitting and the saint is standing above him, and they dispute with each other. The fresco in Peć shows a few peculiarities: the number of the soldiers is by far bigger than in the preserved examples and they surround Maximian, which is a unique arrangement. A sword-carrier behind the throne stands out among them. This is a motive taken from the Byzantine court ceremony, which was not painted often. The construction under which Maximian is sitting with his suite is also specific. It is a free interpretation of the box reserved for emperors and higher officials at the stadium, and not a picture of the palace as has been suggested in the science. The red velum connects this scene with the following one – St.Demetrius blesses St. Nestor (the legend has been preserved). The standard scheme of this scene includes two figures, Demetrius and Nestor. Taking into consideration the way they were presented, the preserved examples testify to the fact that there were several iconographic types in the Byzantine Medieval art. The oldest illustrations of the theme show three seals from the 10th century, perhaps inspired by the representation in the saint’s Basilica in Thessaloniki: Demetrius with the spear and Nestor with or without a weapon, standing opposite each other. A similar solution is shown on the silver tile from a much later date, now in the British Museum in London (Add. Ms 28815, 14th century), where both figures are still standing, and Nestor is accepting the sword from Demetrius` hand. In other examples, Demetrius is sitting whereas Nestor is receiving the blessing, armed for a fight. This iconography can be followed on frescoes in the churches in Kitti, Krokees, and Mistras, as well as on the fresco in Peć. The representation on the Vatopedi reliquary (14th century) also belongs to the scheme. In the later version of the scene in Serbian monasteries of Dečani (north parekklesion dedicated to St.Demetrius, 1335–48) and Marco`s monastery, Nestor is wearing civilian clothes, following the written sources. The icon from Sofia shows the unique iconography. By including a few carefully chosen motives in the composition, the painter from Peć created a specific scene, with a number ofmotives which do not have analogies with the preserved compositions. One more figure is included in the composition, Demetrius`servant Lupus. As far as the representation in the upper part of the scene, with a partly preserved figure kneeling and over which the top parts of the angel’s wings can be seen, it is most likely Nestor to whom the angel showed himself. The written sources do not mention the vision either before or after Nestor’s fight with Lyaeus, but Passio altera describes that, taken before emperor won the victory over Lyaeus, as the answer to the question which kind of magic he used to beat the experienced gladiator, Nestor responds that he was helped by Demetrius’ God who had sent an angel to lead his hand. The small icon hanging on the chain from the prison ceiling could only be seen in Peć, although the motive itself is not unknown from the scenes of this cycle. There is an interesting detail: sella curulis, on which Demetrius is sitting, which as a motive appears on the fresco in Peć can be connected with two early Christian works with representations of Demetrius. These works are preserved in Basilica in Thessaloniki from where the motive could have been accepted into the iconography. There is no scorpion on the painting as is claimed by earlier scholars.